Equipamiento colectivo para el mejoramiento del hábitat rural productivo (2024)
"When speaking of architecture and culture in Colombia, a territory and a particular geographic space are defined beforehand. This territory, the current one, has not been the same over time. Political events have successively modified it..." (Saldarriaga, 2016), communities inhabit geographically and architecturally defined places. A territory represents a way of inhabiting; this inhabiting is a collective fact, and as a collective fact it builds a culture, being architecture the basis on which these ways of inhabiting are built and developed.